(untitled) (International Journal of Contemporary Security Studies, 2023)
In the business environment, information as a means of understanding the world and communication, has taken on the role of a corporate resource that deserves at least as much attention as any other resource that any organization has. When talking about information as a corporate resource, it is indispensable to deal with the issue of its protection. Therefore, the attention of the academic and professional public is already largely occupied by the issue of information security, including the implementation of security and other information resources that act as support for the use of information. Information security is a function that must be continuous due to its importance. On the other hand, every organization is faced with the task of ensuring business continuity due to and after disruptions, regardless of the nature of those disruptions. In this regard, the paper starts from the assumption that one of the prerequisites for the business continuity is the (continuity) of information security. The author will try to present how information security contributes to business continuity management.